Tadalafil 5 mg once daily for the treatment of erectile dysfunction during a 6-month observational study (EDATE): impact of patient characteristics and comorbidities - Hatzichristou, Dimitrios (BMC Urol, 2015)
BACKGROUND: To explore the impact of patient-characteristics and relevant comorbidities on treatment continuation rates, effectiveness, and satisfaction in patients with erectile dysfunction (ED) who started or switched to tadalafil 5 mg once daily (TAD-OaD) at baseline. METHODS: In the EDATE observational study, phosphodiesterase-type-5 (PDE5)-inhibitor pretreated or naïve ED patients who started or switched to TAD-OaD were prospectively followed for 6 months. Time to discontinuation of TAD-OaD was estimated using the Kaplan-Meier product-limit method at Months 2, 4, and 6 in subgroups stratified by age (18 − 65 years and >65 years), PDE5-inhibitor pretreatment, ED-severity (mild, moderate, severe), and presence or absence of relevant comorbidities (BPH, diabetes, CVD, hypertension, dyslipidemia). LSmean change from baseline in International Index of Erectile Function (IIEF) and Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) scores and associated 95 % CIs were assessed using a mixed-model for repeated measures. Visit, ED etiology, and subgroups were included as fixed-effects. RESULTS: Overall, 778 patients received prescriptions for initiating or switching to TAD-OaD at baseline. At Month 2, >90 % of patients remained on TAD-OaD, except those aged >65 years (86.7 %) and patients with severe ED (89.0 %). More than 80 % of patients in all subgroups, except those aged >65 years (75.0 %), continued TAD-OaD at Month 6. There was a significant LSmean negative effect on IIEF- EF domain-score improvement for BPH (LSmean effect [95 % CI]: −2.77 [−4.98, −0.55], p = 0.014), previous PDE5-inhibitor treatment (−2.13 [−3.33,-0.94], p < 0.001), and mild vs moderate ED (-2.00 [−3.54,-0.46], p = 0.011); the latter possibly linked with a bigger treatment-effect in those with more severe ED at baseline. The LSmean effect on change in IIEF-EF was significantly positive for diabetes (2.28 [0.64,3.92], p = 0.007), most likely because those with diabetes had more severe ED at baseline. For all other parameters, no statistically significant LSmean effects in IIEF-EF changes were observed. No comorbidity or baseline-characteristic except age (18 − 65 years vs >65 years: 11.25 [2.96,19.54], p = 0.008) affected changes in EDITS. CONCLUSIONS: Under routine clinical conditions, treatment continuation rate or satisfaction does not seem to be significantly affected by the presence of comorbidities in men who choose ED-treatment with TAD-OaD. The magnitude of treatment effectiveness was affected by certain baseline characteristics and comorbid conditions. TRIAL REGISTRATION: The study (H6D-EW-LVIU) is registered in the German VfA Registry of Non-Interventional Studies (Verband Forschender Arzneimittelhersteller) since 06 December 2011; available at: http://www.vfa.de/de/arzneimittel-forschung/datenbanken-zu-arzneimitteln/nisdb/nis-details/_741. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12894-015-0107-5) contains supplementary material, which is available to authorized users.